2021
DOI: 10.1021/acs.biochem.1c00056
|View full text |Cite
|
Sign up to set email alerts
|

Structural Robustness Affects the Engineerability of Aminoacyl-tRNA Synthetases for Genetic Code Expansion

Abstract: The ability to engineer the substrate specificity of natural aminoacyl-tRNA synthetase/tRNA pairs facilitates the sitespecific incorporation of noncanonical amino acids (ncAAs) into proteins. The Methanocaldococcus jannaschii-derived tyrosyl-tRNA synthetase (MjTyrRS)/tRNA pair has been engineered to incorporate numerous ncAAs into protein expressed in bacteria. However, it cannot be used in eukaryotic cells due to cross-reactivity with its host counterparts. The Escherichia coli-derived tyrosyl-tRNA synthetase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Moreover, while general performance trends are expected to hold upon transferring ncAA incorporation systems between organisms, quantitative differences between organisms can occur, necessitating rigorous characterizations if further SPS implementation is performed in E. coli, mammalian cells, or cells from other organisms. , Despite these important considerations, our results provide several initial demonstrations that, in yeast, SPSs are a comparable format to DPSs.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, while general performance trends are expected to hold upon transferring ncAA incorporation systems between organisms, quantitative differences between organisms can occur, necessitating rigorous characterizations if further SPS implementation is performed in E. coli, mammalian cells, or cells from other organisms. , Despite these important considerations, our results provide several initial demonstrations that, in yeast, SPSs are a comparable format to DPSs.…”
Section: Discussionmentioning
confidence: 96%
“…First, the target enzyme should have low levels of the desired new activity, which in case of PylRS means enzymatic activity toward ncAAs that are highly divergent from the native substrate [ 21 , 22 ]. Second, sufficient stability is required to buffer destabilizing mutations necessary for active site remodeling [ 23 , 24 , 25 ]. Unfortunately, PylRS is marginally stable under standard cultivation conditions in Escherichia coli ( E. coli ) [ 26 ], which is also reflected by the low in vitro solubility of the enzyme [ 20 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that mutants of EcTyrRS often exhibit low thermostabilities. 34 In particular, pBPARS-1 was found to be largely insoluble under ambient conditions, which likely explains its poor activity. Interestingly, a large fraction of pBPARS-3.1 was found in the soluble fraction of the E. coli cell-free extract, while nearly all of pBPARS-1 was found in the insoluble fraction ( Figure S4C ).…”
Section: Resultsmentioning
confidence: 99%